Concurrent Synthesis of High‐Performance Monolayer Transition Metal Disulfides. (9th March 2017) - Sun, Linfeng; Leong, Wei Sun; Yang, Shize; Chisholm, Matthew F.; Liang, Shi‐Jun; Ang, Lay Kee; Tang, Yongjian; Mao, Yunwei; Kong, Jing; Yang, Hui Ying
Abstract : To date, the chemical vapor deposition (CVD) approach has been widely used for the growth of transition metal dichalcogenides (TMDs). However, the reported CVD methods to synthesize TMDs cannot be used to grow more than one type of TMDs. This work reports a promising CVD technique to concurrently synthesize multiple monolayer transition metal disulfides once. The optoelectrical characterization and high‐resolution transmission electron microscopy show the high quality of monolayer crystals, and, more importantly, there is no mixing between different precursors during the growth process, which has been investigated by considering the gas flow dynamics and concentration distribution of precursors in our setup. This strategy indicates the promising future for the batch production of 2D materials and the concurrent synthesis techniques in standard state‐of‐the‐art complementary metal‐oxide‐semiconductor (CMOS) fabrication technology. Abstract : The batch production of monolayer MoS2 and its derivatives grown by chemical vapor deposition techniques is demonstrated. The concurrent synthesis of different 2D materials is also carried out with a uniform crystal quality and high mobility at 64 cm 2 V −1 s −1 (room temperature).